Analysis of Strategy 345 as an Effort to Achieve Participation Targets in BPJS Ketenagakerjaan - Saragih, Tarimantan Sanberto; Mahaganti, Fergie Stevi; Pramasanti, An Nisa; Putra, Mochammad Andika; Bagaskara, Septa; Augustin, Eldest; Fitriani, Kania (Devotion : Journal of Research and Community Service, 2023)
BPJS Ketenagakerjaan has the task and function of administering Employment Social Security through 5 Employment Social Security Programs, namely Employment Injury Insurance Program (EII), Death Benefit Program (DB), Old-Age Benefit Program (OAB), Pension Benefit Program (PB), and Unemployment Insurance Program (UI). The aim of this research is to analyze 345 strategies in an effort to achieve the target of membership in BPJS Ketenagakerjaan. This study used qualitative research methods. The data collection technique in this research is a literature study obtained from Google Scholar and internal research carried out internally at BPJS Ketenagakerjaan. The collected data was analyzed in three stages: data reduction, data presentation, and drawing conclusions. The research results show that the 345 strategy is the right strategy to increase membership with 3 main programs, namely retention, intensification, and expansion, with 4 focuses, namely village ecosystems, market ecosystems, e-commerce and SMEs, and vulnerable workers through 5 engines, namely agency systems, figures, supply chain, auto debit, compliance, and positive supervision. This strategy can increase public awareness, increase coverage, or increase BPJS Ketenagakerjaan participation regarding the benefits of the EII, DB, OAB, PB, and UI programs, as well as increase BPJS Ketenagakerjaan program participants.